Liver SBRT with active motion-compensation results in excellent local control for liver oligometastases: an outcome analysis of a pooled multi-platform patient cohort - Stera, Susanne; Miebach, Georgia; Bürgy, Daniel; Dreher, Constantin; Lohr, Frank; Wurster, Stefan; Rödel, Claus; Marcella, Szücs; Krug, David; Frank A., Giordano; Ehmann, Michael; Fleckenstein, Jens; et al. (Radiotherapy and oncology, 2021)
Background - Local treatment of metastases in combination with systemic therapy can prolong survival of oligo-metastasized patients. To fully exploit this potential, safe and effective treatments are needed to ensure long-term metastases control. Stereotactic body radiotherapy (SBRT) is one means, however, for moving liver tumors correct delivery of high doses is challenging. After validating equal in-vivo treatment accuracy, we analyzed a pooled multi-platform liver-SBRT-database for clinical outcome. - Methods - Local control (LC), progression-free interval (PFI), overall survival (OS), predictive factors and toxicity was evaluated in 135 patients with 227 metastases treated by gantry-based SBRT (deep-inspiratory breath-hold-gating; n = 71) and robotic-based SBRT (fiducial-tracking, n = 156) with mean gross tumor volume biological effective dose (GTV-BEDα/β=10Gy) of 146.6 Gy10. - Results - One-, and five-year LC was 90% and 68.7%, respectively. On multivariate analysis, LC was significantly predicted by colorectal histology (p = 0.006). Median OS was 20 months with one- and two-year OS of 67% and 37%. On multivariate analysis, ECOG-status (p = 0.003), simultaneous chemotherapy (p = 0.003), time from metastasis detection to SBRT-treatment (≥2months; p = 0.021) and LC of the treated metastases (≥12 months, p < 0.009) were significant predictors for OS. One- and two-year PFI were 30.5% and 14%. Acute toxicity was mild and rare (14.4% grade I, 2.3% grade II, 0.6% grade III). Chronic °III/IV toxicities occurred in 1.1%. - Conclusions - Patient selection, time to treatment and sufficient doses are essential to achieve optimal outcome for SBRT with active motion compensation. Local control appears favorable compared to historical control. Long-term LC of the treated lesions was associated with longer overall survival.